Respuesta :
Answer:
[tex]\boxed{\boxed{B.\ f(x)=15(2^2)^{\frac{x}{2}}}}[/tex]
Step-by-step explanation:
The general equation for exponential growth is,
[tex]y=a(1+r)^x[/tex]
where,
a = initial amount,
r = rate of growth,
y = future amount,
x = time.
The function [tex]f(x) = 15(2)^x[/tex] represents the growth of a frog population every year in a remote swamp.
where 15 is the initial amount of frog.
As Elizabeth wants to manipulate the formula to an equivalent form that calculates every half-year, so putting [tex]x=\dfrac{x}{2}[/tex] in the general function,
[tex]y=15(1+r)^{\frac{x}{2}}[/tex]
Now we have to find the value of r.
As we will get same future amount, irrespective to the function used, so comparing the old function with the new function,
[tex]\Rightarrow 15(1+r)^{\frac{x}{2}}=15(2)^x[/tex]
Multiplying the exponents of both sides by [tex]\dfrac{1}{x}[/tex]
[tex]\Rightarrow (1+r)^{\frac{x}{2}\times \frac{1}{x}}=(2)^{x\times \frac{1}{x}}[/tex]
[tex]\Rightarrow (1+r)^{\frac{1}{2}}=(2)^1[/tex]
Squaring both sides,
[tex]\Rightarrow (1+r)=(2)^2=4[/tex]
[tex]\Rightarrow r=4-1=3[/tex]
Putting the value of r, in the general equation,
[tex]y=15(1+3)^{\frac{x}{2}}=15(4)^{\frac{x}{2}}=15(2^2)^{\frac{x}{2}}[/tex]